PELAKSANAAN PERJANJIAN KERJASAMA PENGANGKUTAN BAHAN BAKAR MINYAK BIO SOLAR ANTARA PT PLN (PERSERO) UNIT PELAKSANA PELAYANAN PELANGGAN DENGAN PT RATAH INDAH DI SAMARINDA - Azik Kurniawan (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACT Transportation as an agreement is always preceded by an agreement between the carrier and the shipper. In the transport agreement, the carrier can be said to have acknowledged receiving the goods and undertakes to bring them to the designated place and deliver them to the addressed person. Some of the problems that arise in this study are how the implementation of the Bio Solar Oil Fuel (BBM) transportation agreement and what problems arise in the implementation of the Bio Solar Oil Fuel transportation agreement between PT PLN (Persero) Unit Pelayanan Pelaksana Pelanggan with PT Ratah Indah of Samarinda.The approach method used is a sociological juridical approach. This juridical-empirical research approach uses secondary data as the initial data, which is then followed by primary data. Primary data were obtained by field research, such as direct observation of the implementation of the cooperation agreement for the transportation of Bio Solar fuel. While secondary data is obtained through primary legal materials, secondary legal materials, and tertiary legal materials. The data collection tools used in this research are document studies and interviews, which are then analyzed qualitatively.Based on the results of the study, it is known that the implementation of the transportation cooperation agreement between PT PLN (Persero) Unit Pelayanan Pelaksana Pelanggan with PT Ratah Indah of Samarinda has been carried out in accordance with the agreement that has been agreed by both parties, which contains the rights and obligations between the two parties as well as technical procedures for the implementation of the work starting from the stage of transportation, acceptance, testing, and measurement. The problem of delays in the delivery of Bio Solar fuel in principle is determined by the weather conditions at that time, based on real conditions in the field, the incident is included in the result of force majeure, this is evidenced by PT Ratah Indah with a written letter from the Samarinda Department of Transportation, so that all delays or failures will not result in a claim for compensation for losses suffered by other parties and is related to the difference in volume between the amount of Bio Solar fuel listed in the Bill of Loading (B/L) or Loading Order Liters 15°C with a physical received by PT PLN, then the shortage is the responsibility of the Carrier and must replace the difference/shortage of Bio Solar BBM within 7 x 24 hours. Keywords: Agreements, Transportation, Bio Solar